Communicating in science : writing a scientific paper and speaking at scientific meetings - Booth, Vernon ([S.l.] : Cambridge University Press, 1993)
This concise, straightforward book will help workers in all scientific disciplines to present their results effectively. Chapters include: "Writing a Scientific Paper" "Before You Lecture or Talk to Us, Please Read This" "Empty Numbers" "Preparation of the Script and Figures" "For Those to Whom English is a Foreign Language" "Preparation of a Doctoral Dissertation or Thesis"